Risk of Suicidal Behaviors and Antidepressant Exposure Among Children and Adolescents: A Meta-Analysis of Observational Studies - Li, Kuan; Zhou, Guibao; Xiao, Yan; Gu, Jiayu; Chen, Qiuling; Xie, Shouxia; Wu, Junyan (Frontiers in Psychiatry, 2022)
Objectives: Although several studies have reviewed the suicide risk of antidepressants, the conclusions remain inconsistent. We therefore performed a meta-analysis of observational studies to address the association between exposure of antidepressants, especially selective serotonin reuptake inhibitors (SSRIs), and risk of suicide and suicide attempt in children and adolescents. Methods: MEDLINE and Embase were searched from January 1990 up to April 2021. Seventeen cohort and case-control studies were identified that reported suicide or suicide attempt in children and young adults (aged 5-25 years) who were exposed to any antidepressants. We extracted the estimates and corresponding 95% confidence intervals (CI) from each publication. Results: The results showed that antidepressant exposure significantly increased the risk of suicide and suicide attempt when compared with no antidepressants usage among children and adolescents. The pooled relative risk (RR) was 1.38 (95% CI 1.16 to 1.64; I2= 83.1%). Among the antidepressants, SSRI use was associated with increased risk of suicide and suicide attempt, and the pooled RR was 1.28 (95% CI 1.09 to 1.51; I2= 68.8%). In subgroup analysis, the attempted suicide risk of antidepressant and SSRI was significantly increased (RR=1.35, 95% CI 1.13-1.61; I2= 86.2% for all antidepressants; and RR=1.26, 95% CI 1.06-1.48; I2= 73.8% for SSRIs), while the completed suicide risk of antidepressant and SSRI was not statistically significant (RR=2.32, 95% CI 0.82-6.53; I2= 6.28% for all antidepressants; and RR=1.88, 95% CI 0.74-4.79; I2= 52.0% for SSRIs). In addition, the risk of suicide and suicide attempt between SSRI and other antidepressants was similar (RR 1.13, 95% CI: 0.87 to 1.46, I2= 32.4%). Conclusion: The main findings of this meta-analysis provide some evidence that antidepressant exposure seems to have an increased suicidal risk within children and young adults. Since Untreated depression remains the one of the largest risk factors for suicide, and the efficacy of antidepressants is proven, clinicians should evaluate carefully their patients and be cautious with patients at risk to have treatment emergence or worsening of suicidal ideation (TESI/TWOSI) when prescribing antidepressants to children and young patients.